Aquarium Monitoring and Automatic Feeding System Based on Internet of Things - Faisal Noer Muhamad; Depik Toni Yulianto; Muhammad Aldi Aulia Fathurohman (International Journal of Research and Applied Technology (INJURATECH), 2023)
Now day ornamental fish enthusiasts are increasing, this is in line with the increasing number of people who have a hobby of keeping ornamental fish. In maintaining ornamental fish, several things must be considered to maintain the health of the fish, including water quality, changes in water temperature, and feeding. Therefore, to maintain the health of ornamental fish, a system is needed to monitor the aquarium's condition in real-time. This research aims to design a system that can monitor the aquarium's condition and provide feed automatically. Monitoring is carried out by utilizing Internet of Things (IoT) technology, which allows the information collected to be accessed in real-time through the Smart Aquarium application. The research method used in this research is analysis with a qualitative approach. The results showed that this automatic monitoring and feeding system can maintain health and reduce the risk of death of ornamental fish in the aquarium. The main concept of this system is monitoring water temperature conditions, water ph levels, and water turbidity, and doing automatic feeding. In addition, this system also has a feature that can see the current conditions in the aquarium. This system can make it easier for ornamental fish owners to monitor the conditions of the aquarium and can provide peace of mind when leaving the aquarium for some time.